Analysis of player heart rate and stroke success in tennis drill scenarios - Balci, Ibrahim Cem; Cicek, Buse; Sayin, Irem; Salturk, Serkan; Sarialioglu, Onur; Ozel, Deniz; Kakulia, Nika; Demircali, Ali Anil; Uvet, Huseyin (FRONTIERS MEDIA SA, 2026)
Heart rate (HR) is a practical indicator of physiological load and arousal, yet its shot by shot relationship with tennis performance remains insufficiently characterized. We quantified associations between HR and stroke outcome and spatial accuracy during a standardized target based drill. The dataset comprised 8,197 shots from 23 players across 93 training sessions. HR was sampled at 1 Hz and temporally aligned to each shot using a fixed +/- 5 s window around the shot reference time, enabling the extraction of absolute HR levels, short term HR changes and HR intensity zones. Shot outcomes (successful/unsuccessful) and distance to the nearest target area corner were obtained using a camera based tracking system. Successful strokes were generally associated with lower HR levels (p< 0.001; small effects, r approximate to 0.17). Short term HR dynamics provided limited additional discrimination, with only pre-shot change showing a small difference between outcomes. HR intensity zones were associated with success (p< 0.001), with a greater proportion of successful strokes occurring in lower zones (Zones 1-3). Accounting for repeated shots within sessions and players, mixed-effects models were additionally fitted. Higher HR remained associated with lower odds of shot success (OR per 10 bpm = 0.957, 95% CI 0.953-0.961) and a model using heart rate at the shot instant yielded very similar estimates. The continuous distance outcome showed weaker evidence after hierarchical adjustment. Overall, shot-aligned HR monitoring may provide useful contextual information for interpreting performance during precision-focused drills. However, the modest effect sizes suggest that HR should be considered alongside technical and task-related indicators rather than as a primary basis for training decisions.
Keywords: athlete performance; heart rate; shot success; sport; statistical analysis; tennis; PERFORMANCE-CHARACTERISTICS; FATIGUE; VARIABLES; Physiology